2024
DOI: 10.1101/2024.04.23.590808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent neural circuits for proprioceptive and exteroceptive sensing of theDrosophilaleg

Su-Yee J. Lee,
Chris J. Dallmann,
Andrew Cook
et al.

Abstract: Somatosensory neurons provide the nervous system with information about mechanical forces originating inside and outside the body. Here, we use connectomics to reconstruct and analyze neural circuits downstream of the largest somatosensory organ in theDrosophilaleg, the femoral chordotonal organ (FeCO). The FeCO has been proposed to support both proprioceptive sensing of the fly's femur-tibia joint and exteroceptive sensing of substrate vibrations, but it remains unknown which sensory neurons and central circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 91 publications
0
0
0
Order By: Relevance
“…Claw extension sensing neurons connect to two 13A neurons that inhibit tibia extensor MNs. These neurons also directly connect to tibia flexor MNs 23 . Together, extension-sensing proprioceptors activate flexor MNs and 13A neurons that inhibit extensor MNs, possibly inducing a switch from extension to flexion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Claw extension sensing neurons connect to two 13A neurons that inhibit tibia extensor MNs. These neurons also directly connect to tibia flexor MNs 23 . Together, extension-sensing proprioceptors activate flexor MNs and 13A neurons that inhibit extensor MNs, possibly inducing a switch from extension to flexion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, flexion position-sensing proprioceptors activate 13As that inhibit medial joint flexion. Recent connectomics analysis showed that flexion sensing proprioceptors send direct excitatory feedback to tibia extensor MNs and indirect inhibitory feedback to tibia flexor MNs 23 . Together, flexion sensing proprioceptors directly activate the extensor MNs, and inhibit the tibia flexor MNs by activating primary 13A neurons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early access to the proofread and annotated connectome data that we describe has already enabled and assisted a range of exciting work including studies of the circuit basis of locomotor behaviour and the organisational and functional logic of descending neurons (Braun et al, 2024; H. S. J. Dallmann et al, 2024;Lee et al, 2024;Lesser et al, 2024;Sapkal et al, 2023;von Reyn et al, 2024 unpublished;Yang et al, 2023). The sensorimotor reconstructions presented enable us to infer the circuit basis of behaviours, including sexually dimorphic patterns, allowing us to formulate new hypotheses regarding numerous circuit components.…”
Section: Discussionmentioning
confidence: 95%
“…We have established a platform for systematic neuron typing based on light-level and cross-dataset identification, which we encourage the community to utilise for studying their specific circuits of interest. Pre-publication access to our work has already benefited a number of publications ( Braun et al, 2023 ; H. S. J. Cheong et al, 2024 ; Dallmann et al, 2024 ; Lee et al, 2024 ; Lesser et al, 2024 ; Sapkal et al, 2023 ; Yang et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%